2014
DOI: 10.1111/bph.12690
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline decreases ethanol intake and increases dopamine release via neuronal nicotinic acetylcholine receptors in the nucleus accumbens

Abstract: Background and PurposeVarenicline, a neuronal nicotinic acetylcholine receptor (nAChR) modulator, decreases ethanol consumption in rodents and humans. The proposed mechanism of action for varenicline to reduce ethanol consumption has been through modulation of dopamine (DA) release in the nucleus accumbens (NAc) via α4*-containing nAChRs in the ventral tegmental area (VTA). However, presynaptic nAChRs on dopaminergic terminals in the NAc have been shown to directly modulate dopaminergic signalling independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 58 publications
(79 reference statements)
5
42
3
Order By: Relevance
“…Because varenicline is also a potent partial agonist of α4β2 nAChRs, our results corroborate the suggestion that α4β2 nAChRs in the VTA are not involved in cue-driven alcohol-seeking (Löf et al, 2007). Doses used in the present study (2 and 4 μg/0.3 μl/hemisphere) were higher than those employed in an earlier report in which intra-VTA varenicline (1 and 2 μg/0.5 μl/hemisphere) had no impact on oral alcohol intake (Feduccia et al, 2014). Future studies should test lower varenicline doses before ruling out the VTA as a neural target for the action of varenicline, as low varenicline doses sometimes produce effects that are not observed at high doses (Guillem and Peoples, 2010;Wouda et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Because varenicline is also a potent partial agonist of α4β2 nAChRs, our results corroborate the suggestion that α4β2 nAChRs in the VTA are not involved in cue-driven alcohol-seeking (Löf et al, 2007). Doses used in the present study (2 and 4 μg/0.3 μl/hemisphere) were higher than those employed in an earlier report in which intra-VTA varenicline (1 and 2 μg/0.5 μl/hemisphere) had no impact on oral alcohol intake (Feduccia et al, 2014). Future studies should test lower varenicline doses before ruling out the VTA as a neural target for the action of varenicline, as low varenicline doses sometimes produce effects that are not observed at high doses (Guillem and Peoples, 2010;Wouda et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…However, varenicline in the NAc but not VTA reduced voluntary alcohol consumption in rats, highlighting a role for nAChRs in the NAc in alcohol reinforcement (Feduccia et al, 2014). As the present studies found that systemic varenicline reduced context-induced relapse to alcohol-seeking, we examined the effect of intra-NAc or intra-VTA varenicline on this behavior to determine the neural loci of varenicline's effects.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations